Effects of Omnichannel Marketing, Product Quality and Customer Engagement on Uniqlo Customer Loyalty - Desi Listiyani; Danang Kurniawan; Nurliya Apriyana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The fashion retail industry in Indonesia is experiencing rapid growth, mainly driven by lifestyle changes and the development of digital technology. However, the COVID-19 pandemic has had a huge negative impact on this sector. A decline in sales occurred due to social restrictions and the shift of consumers to online shopping. To survive, many retail companies, including fashion industry players, adopted an omnichannel strategy that integrates online and offline sales. With a combination of physical stores, e-commerce platforms, and strong promotional strategies on social media, it is expected to reach more consumers and increase customer loyalty. In addition, high product quality and good customer engagement is one of the supporting factors in building customer loyalty. Uniqlo, being a Japanese appareal brand that is quite successful in Indonesia. Moreover, it was able to survive amid the COVID-19 pandemic that hit at that time. Through empirical testing and data analysis, this study aims to prove the positive and significant influence between Omnichannel Marketing, Product Quality, and Customer Engagement with Customer Loyalty on Uniqlo clothing products. Testing was carried out using quantitative methods to analyze all existing variables and sampling techniques using  purposive sampling techniques. The respondents totaled 102 people. Primary data was collected through an online questionnaire (Google Form) for one month. Data analysis using multiple linear regression with the help of SPSS software version 30 of 2024. The results of this study indicate that Omnichannel Marketing, Product Quality and Customer Engagement have a positive influence on Customer Loyalty. With these positive significance results and understanding the relationship between these factors is expected to provide insight for companies to develop more effective marketing strategies and increase market share.